Intracranial pressure elevation post-stroke: Mechanisms and consequences - Hood, Rebecca J.; Beard, Daniel J.; McLeod, Damian D.; Murtha, Lucy A.; Spratt, Neil J. (Frontiers in Stroke, 2023)
Intracranial pressure (ICP) elevation post-stroke has long been thought of as a cause of secondary deterioration after large, malignant infarction, and dramatic ICP elevation is frequently a pre-terminal event. However, there is an increasing body of evidence to suggest that ICP also rises after small stroke, typically within 24 hours of the infarct. The timing of this rise suggests that it may play an important role in the collateral failure associated with early infarct expansion. Despite its increasingly recognized importance to patient outcome, very little is currently known about the underlying mechanisms of ICP elevation post-stroke. The traditional understanding suggests ICP elevation occurs solely due to cerebral edema, however this does not seem to be the case in mild-moderate infarction. Instead, recent studies suggest a role for changes in cerebrospinal fluid (CSF) volume. In this article, we will discuss recent mechanistic observations, as well as the consequences of ICP elevation post-stroke.